The Use of Learning Media in Islamic Religious Education Learning to Grow Students' Interest in Learning - Yuliharti, Yuliharti (International Journal of Demos (IJD), 2022)
AbstractIslamic Religious Education known as PAI is one of the compulsory subjects taught in schools. However, PAI is less desirable and is considered boring by most students. To achieve the goals of Islamic religious education, in the learning process, teachers can use learning media to make it easier to teach the subject matter, and students more easily understand the lesson, therefore this study has the aim of how the use of learning media in Islamic religious education subjects can increase interest in learning student. This study uses a qualitative approach with descriptive analysis of research results. From the research, it was found that teachers who have competence, if they can choose the right methods and media in PAI learning with their characteristics, will be able to present learning in a solid formula. Learning will be fun for students to internalize religious values in PAI learning materials. Indirectly it can also motivate students to develop themselves and find beautiful pearls in Islamic religious education materials to shape their morals and character.Keywords: Learning Media, Islamic Religious Education, Religious Values.Â AbstrakPendidikan Agama Islam yang dikenal dengan PAI merupakan salah satu mata pelajaran wajib yang diajarkan di sekolah. Namun, PAI kurang diminati dan dianggap membosankan oleh sebagian besar siswa. Untuk mencapai tujuan pendidikan agama Islam, dalam proses pembelajaran guru dapat menggunakan media pembelajaran agar lebih mudah dalam mengajarkan materi pelajaran, dan siswa lebih mudah memahami pelajaran, oleh karena itu penelitian ini memiliki tujuan bagaimana pemanfaatan media pembelajaran. dalam mata pelajaran pendidikan agama Islam dapat meningkatkan minat belajar siswa. Penelitian ini menggunakan pendekatan kualitatif dengan analisis deskriptif hasil penelitian. Dari penelitian ditemukan bahwa guru yang memiliki kompetensi, jika dapat memilih metode dan media yang tepat dalam pembelajaran PAI dengan karakteristiknya, akan mampu menyajikan pembelajaran dalam formula yang solid. Pembelajaran akan menyenangkan bagi siswa untuk menginternalisasikan nilai-nilai agama dalam materi pembelajaran PAI. Secara tidak langsung juga dapat memotivasi siswa untuk mengembangkan diri dan menemukan mutiara yang indah dalam materi pendidikan agama Islam untuk membentuk akhlak dan akhlaknya.Kata Kunci: Media Pembelajaran, Pendidikan Agama Islam, Nilai-nilai Keagamaan.